Employee Satisfaction of PT Bukit Asam TBK'S Development Program - Haniyah Qurratul `Aini; Alldila Nadhira Ayu Setyaning (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to evaluate employee satisfaction with the development program at PT Bukit Asam Tbk. The research approach used is descriptive quantitative by collecting primary data through questionnaire surveys and observations and secondary data from company statistical datasets. The results showed that in 2022, PT Bukit Asam Tbk has realized training programs for 992 employees. The level of employee satisfaction with the training material, instructor's ability, and training atmosphere showed an average value of 3.8 (agree). Furthermore, the assessment of supervisor and coworker satisfaction with employee performance after training received an average value of 3.7 (effective). This indicates that the development program conducted by PT Bukit Asam Tbk has a positive impact on improving employee performance. This study recommends that companies use information systems to facilitate the management of employee data and training programs and provide opportunities for employees to propose training according to their needs.